Donor ICT strategies matrix CD-Rom (OECD ParisFR, 2003)
Aims at compiling information on how bilateral and multilateral donors have mainstreamed ICT in their development assistance programmes in order to achieve development goals, particularly the Millennioum Development Goals.
Keywords: DEVELOPMENT AID